The Weakening Relations between Turkey-America in The Field of Defence and Security in 2015-2019 - Dwi Ardiyanti; Aulia Srifauzi; Habib Alfarisi (International Journal of Educational Research & Social Sciences, 2021)
Turkey and the United States of America have long built cooperation in the security and defense sector since the Cold War. Turkey was a strategic region for the USA as a path to stick to the hegemony in the Middle East. The Weakening cooperation between Turkey and the USA happened since the USA was no longer on the same path as Turkey. The coup d’état that happened in Turkey was also one of the reasons for weakening cooperation between Turkey and the USA. Turkey then built cooperation with NATO (North Atlantic Treaty Organization) and actively involved in the war against ISIS. The withdrawal of the USA’s Missiles from Turkey’s borders caused Turkey then bought missiles from Russia, which has been so only criticized by NATO and the USA. In the research, the writer analyzed the factor causing the weakening cooperation between Turkey and the USA in the security and defense field. The researcher used Neorealism theory, in which neorealism believed that anarchy in the international system would make a country build the relations of cooperation with another country, then the balance of power concept was also used to see the interest of the USA in building cooperation with Turkey